Identity, Cosmopolitanism and Education in extreme metal bands: the case of Finland - Otero Urtaza, Eugenio (Historia y Memoria de la Educación, 2020)
Music is an art that often defines the education and values of people. Extreme Metal is a controversial musical genre that at times, in some of its subgenres, has caused episodes of exceptional violence. Metalheads make up a cultural movement that is present on all continents. Metal currents are difficult to dissolve in the magma of social acceptance: they create a consciousness of transnational solidarity, of response to waste and ostentation that destroys the planet, while claiming the place in which it is lived. Extreme Metal is not an artistic fashion, it is profoundly changing the mentality of many young people who reject the social organisation of the capitalist and Christian world and try to find alternatives for the future. In this article we ask how their convictions are formed and in what way the school's teachings influence them. One of the ways of studying the phenomenon is by analysing the lyrics of the songs. Not all subgenres can be covered and three Melodic Death Metal bands from Finland have been chosen for study, especially in relation to their feelings about nature and the cosmos. It is evident that their songs are often based on classical and popular poems learned at school? by the legacy left by the great Finnish poets, and even by the literary creations of musicians for that school resonance.